1998
DOI: 10.1523/jneurosci.18-19-07881.1998
|View full text |Cite
|
Sign up to set email alerts
|

Basic FGF Increases Communication between Cells of the Developing Neocortex

Abstract: We have found that basic fibroblast growth factor (bFGF), applied to cortical progenitor cells in vitro, produces an increase in the expression of the gap junction protein connexin (Cx) 43 and in the mRNA encoding Cx 43. This effect was evident in both proliferating and nonproliferating cells. The elevated levels of mRNA suggest that bFGF is likely to exert its effect by upregulating the rate of transcription of the Cx 43 gene. We have further shown that the increase in Cx 43 expression is mediated through the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 50 publications
0
32
0
Order By: Relevance
“…In vertebrates, growth factors have been shown to selectively diminish (Maldonado et al, 1988;Madhukar et al, 1989;Lau et al, 1992) or enhance (Pepper et al, 1989;Nadarajah et al, 1998;Reuss et al, 1998;Aberg et al, 2000) coupling and connexin expression. In Helisoma, it is believed that trophic factors are among the substances released from isolated ring ganglia when conditioning defined medium (Wong et al, 1981(Wong et al, , 1983(Wong et al, , 1984Barker et al, 1982).…”
Section: Neurotrophic Effects On Synaptic Developmentmentioning
confidence: 99%
“…In vertebrates, growth factors have been shown to selectively diminish (Maldonado et al, 1988;Madhukar et al, 1989;Lau et al, 1992) or enhance (Pepper et al, 1989;Nadarajah et al, 1998;Reuss et al, 1998;Aberg et al, 2000) coupling and connexin expression. In Helisoma, it is believed that trophic factors are among the substances released from isolated ring ganglia when conditioning defined medium (Wong et al, 1981(Wong et al, , 1983(Wong et al, , 1984Barker et al, 1982).…”
Section: Neurotrophic Effects On Synaptic Developmentmentioning
confidence: 99%
“…Transfer of Lucifer Yellow was determined by fluorescence microscopy using filter set 05 (395-440 nm/ 460-470 nm; Zeiss, UK) on an Axiostat microscope (Zeiss, UK). Inhibition of dye transfer was quantified by determining the percentage of injected cells that communicated Lucifer Yellow to < 5, 5-10 and > 10 neighbouring cells (Nadarajah et al 1998). …”
Section: Dye Transfermentioning
confidence: 99%
“…Several studies have shown that connexins accumulate in intracellular stores that correspond to the ERGIC/Golgi in cultured cells (16 -18) and tissues (19), and growth factors appear to regulate connexin transport between these stores and the gap junction (20). Transport of membrane proteins in general from such intracellular stores to the plasma membrane is likely to involve tubulovesicular networks (21,22).…”
mentioning
confidence: 99%